Ecological Assets and Academic Procrastination among Adolescents: The Mediating Role of Commitment to Learning - Chen, Bin-Bin; Han, Wen (Frontiers in Psychology, 2017)
Academic procrastination is defined as a purposive delay of academic tasks that must be completed. Within the framework of the ecological model of resiliency, this study examined how ecological assets were related to academic procrastination among adolescents. Participants in the study were 577 adolescents (53.5% boys) from Shanghai, China. They completed measures of ecological assets, commitment to learning, and academic procrastination. Structural equation modeling revealed that, as predicted, ecological assets were negatively associated with academic procrastination. In addition, commitment to learning fully mediated the association between ecological assets and academic procrastination. Implications of the present findings are discussed.